Percutaneous image guided electrochemotherapy of hepatocellular carcinoma - Djokić, Mihajlo (Radiology and oncology (Ljubljana), 2020)
Background. Electrochemotherapy is an effective treatment of colorectal liver metastases and hepatocellular carcinoma (HCC) during open surgery. The minimally invasive percutaneous approach of electrochemotherapy has already been performed but not on HCC. The aim of this study was to demonstrate the feasibility, safety and effectiveness of electrochemotherapy with percutaneous approach on HCC. Patient and methods. The patient had undergone the transarterial chemoembolization and microwave ablation of multifocal HCC in segments III, V and VI. In follow-up a new lesion was identified in segment III, and recognized by multidisciplinary team to be suitable for minimally invasive percutaneous electrochemotherapy. The treatment was performed with long needle electrodes inserted by the aid of image guidance. Results. The insertion of electrodes was feasible, and the treatment proved safe and effective, as demonstrated by control magnetic resonance imaging. Conclusions. Minimally invasive, image guided percutaneous electrochemotherapy is feasible, safe and effective in treatment of HCC.
Keywords: elektrokemoterapija; hepatocelularni rak; jetra; minimalna invazivnost